GDNF-based therapies, GDNF-producing interneurons, and trophic support of the dopaminergic nigrostriatal pathway. Implications for Parkinson’s disease - d’Anglemont de Tassigny, Xavier; Pascual, Alberto; López-Barneo, José (Frontiers in Neuroanatomy, 2015)
The glial cell line-derived neurotrophic factor (GDNF) is a well-established trophic agent for dopaminergic (DA) neurons in vitro and in vivo. GDNF is necessary for maintenance of neuronal morphological and neurochemical phenotype and protects DA neurons from toxic damage. Numerous studies on animal models of Parkinson’s disease (PD) have reported beneficial effects of GDNF on nigrostriatal DA neuron survival. However, translation of these observations to the clinical setting has been hampered so far by side effects associated with the chronic continuous intra-striatal infusion of recombinant GDNF. In addition, double blind and placebo-controlled clinical trials have not reported any clinically relevant effect of GDNF on PD patients. In the past few years, experiments with conditional Gdnf knockout mice have suggested that GDNF is necessary for maintenance of DA neurons in adulthood. In parallel, new methodologies for exogenous GDNF delivery have been developed. Recently, it has been shown that a small population of scattered, electrically interconnected, parvalbumin positive (PV+) GABAergic interneurons is responsible for most of the GDNF produced in the rodent striatum. In addition, cholinergic striatal interneurons appear to be also involved in the modulation of striatal GDNF. In this review, we summarize current knowledge on brain GDNF delivery, homeostasis, and its effects on nigrostriatal DA neurons. Special attention is paid to the therapeutic potential of endogenous GDNF stimulation in PD.